Prediksi prospek harga saham perusahaan perbankan Menggunakan Regresi Linear (Study Kasus Bank BCA Tahun 2015-2017) - Merfin Keren; Raymond Sunardi Oetama (Jurnal Sistem Informasi, 2019)
The method to be used in this paper is Linear Regression using Excel tools to perform calculations and SPSS 16.0 as a data mining tool. The research data taken is historical data of banking companies for 3 periods as a whole in the form of excel that has been downloaded from the Yahoo Finance website with the final results are in the form of MAPE charts in 3 years period, graphs of closing vs prediction price comparison and recommendations for investors to start shares.